Neurophysiological Changes in the First Year After Cell Transplantation in Sub-acute Complete Paraplegia - Santamaria, Andrea J.; Benavides, Francisco D.; Saraiva, Pedro M.; Anderson, Kimberly D.; Khan, Aisha; Levi, Allan D.; Dietrich, W. Dalton; Guest, James D. (Frontiers in Neurology, 2021)
Circuit reorganization after spinal cord injury (SCI) is essential to functional recovery. The clinical examination may be insensitive and result in false-negative conclusions regarding the therapeutic activity of interventions. Neurophysiologic techniques have the sensitivity to detect changes to provide proof-of-concept of a therapeutic effect and direct further intervention development to increase recovery. We previously reported a Phase 1 study in which we transplanted autologous purified Schwann cells into the injury epicenter of participants with complete subacute thoracic SCI, observing no clinical improvements. Here, we report the longitudinal electrophysiological assessments of the trial. Six participants underwent neurophysiology screening pre-transplantation and had three subsequent post-transplantation assessments, including MEPS, SSEPs, voluntarily triggered EMG and GSR. We found many changes not detectable by clinical exam. Importantly, these included progressive recovery of voluntary activation of leg and foot muscles, potentiated by supraspinal Jendrassik maneuvers. The assigned clinical neurological level missed increasing motor connectivity, many segments below the level in the intercostal and abdominal muscles in all subjects. Galvanic skin testing revealed significant autonomic dysfunction in the hands well above the injury levels. Of all tests, voluntary EMG appeared most sensitive. These consistent findings challenge the current conceptualization of complete paraplegia with a single level. Neurophysiology studies are sensitive tools to measure neural connectivity that should be utilized in therapeutics trials to detect therapeutic activity.